Pengembangan Media Pembelajaran Interaktif Berbasis Weblog Blogger Pada Materi Konsep Ilmu Ekonomi Kelas X IPS SMA NWDI Pancor - Hernika; Muhammad, Farhana (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2023)
This study aims to: (1) determine the effectiveness of the development of interactive learning media based on blogger weblogs on the material of economics concepts for class X IPS SMA NWDI PANCOR, and (2) to determine the responses of teachers and students to the development of interactive learning media based on blogger weblogs on the material of economics concepts for class X IPS SMA NWDI PANCOR. The development procedure uses the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The trial subjects were students of class X IPS SMA NWDI PANCOR. Data collection used assessment sheets of material experts and media experts, student response questionnaires and teacher responses, and student learning outcomes. The results of the study showed that the assessment of material experts obtained a score of 74% included in the good category and the assessment of media experts obtained a score of 86% included in the very good category. And seen from the teacher's response obtained a score of 86% included in the very good category, the student's response obtained a score of 85% included in the very good category. It can be concluded that interactive learning media based on blogger weblogs is quite effective in improving student learning outcomes in the material of economic science concepts.